The werther effect of two celebrity suicides: an entertainer and a politician. - Jae-Hyun Kim (Public Library of Science (PLoS), 2013)
Purpose Suicide is a major health problem in Korea. Extensive media exposure of celebrity suicide may induce imitative suicide, a phenomenon called the Werther effect. We examined the increased suicide risk following the suicides of an entertainer and a politician, and identified the relative suicide risks. Methods News articles about the celebrity suicides were obtained from three major newspapers and analysed for quantitative and qualitative features. Imitative suicide risk was investigated by applying a Poisson time series autoregression model with suicide mortality data from the National Statistics Office for 1.5 years before and 1.5 years after each celebrity's suicide. The period with a significantly increased number of suicides immediately after the celebrity's suicide determined the Werther effect band. The relative risk during this period was examined for different ages, genders, and suicide methods. Results News reports were more numerous and they contained more positive definitions about the entertainer's suicide. The risk of suicide deaths rose markedly after both celebrity suicides. However, the Werther effect band was longer for the entertainer (6 weeks) than for the politician (4 weeks). The relative suicide risk was significant for almost all ages and both genders during that of both individuals. Use of the same suicide method was a prominent risk factor after both celebrity suicides. Conclusions Our results confirm the existence of imitative suicide behaviours, suggesting a facilitation effect of media reports. Guidelines for responsible media reporting need to be implemented to enhance public mental health in Korea.